Marine ornamental shrimp : - Calado, Ricardo (Wiley-Blackwell Pub., 2008)
Marine Ornamental Shrimp is an important and extremely timely publication which will be an essential reference and manual for all those involved in the trade and culture of marine ornamental species, including aquaculture scientists and personnel in aquaria. Conservation biologists and invertebrate zoologists will also find much of importance within this book.